2012
DOI: 10.1682/jrrd.2011.05.0087
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and transcutaneous oxygen pressure in men with spinal cord injury

Abstract: Abstract-This pilot study proposed a method for assessing the status of vascular flow measured by transcutaneous oxygen pressure (TcPO2) in the area of the ischium in people with spinal cord injury (SCI). In a sample of 38 men (two groups: 12 physically active and 26 sedentary) with thoracic SCI, the distribution of the physiological response of the tissues under load during sitting was assessed through analysis of ischium TcPO2 values obtained by an oximeter. TcPO2 baseline, recovery time of TcPO2 after sitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…Using the ES-shorts, muscle contractions decreased during the stimulation cycles, which is most likely due to fatigue of fast fatigue type 2 muscle fibers [27][28][29][30][31]. After SCI, composition of muscle fibers in muscles below the lesion level shifts towards fast fatigue muscle fibers [32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Using the ES-shorts, muscle contractions decreased during the stimulation cycles, which is most likely due to fatigue of fast fatigue type 2 muscle fibers [27][28][29][30][31]. After SCI, composition of muscle fibers in muscles below the lesion level shifts towards fast fatigue muscle fibers [32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Crespo Ruiz et al 13 described the physiological training effects: muscles will enlarge and become stronger and circulation will improve. ES-induced muscle activation with tetanic contractions allows mechanically unrestricted BF and may lead to less fatigue as a result of changes in tissue.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 This may exert a decisive influence on the capacity to transport oxygen in the areas most affected by disuse resulting from the SCI itself. This is especially important when prolonged treatment is required, for example, in an attempt to prevent PUs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Studies in SCI have reported that regular PA can lead to an improved health condition by reducing cardiovascular risks, 4 pain, 5 the risk for shoulder pain and depressive symptoms, 6 and the risk for developing pressure injuries. 7 On the other hand, it is known from literature that too high amounts of PA in wheelchair athletes result in severe shoulder complications including chronic pain. 8 However, long-term studies correlating the amount of PA with the development of musculoskeletal complications are missing.…”
Section: Introductionmentioning
confidence: 99%